2016
DOI: 10.1158/1078-0432.ccr-15-2502
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin Containing TCP-1 Protein Level in Breast Cancer Cells Predicts Therapeutic Application of a Cytotoxic Peptide

Abstract: Purpose: Metastatic disease is a leading cause of death for patients with breast cancer, driving the need for new therapies. CT20p is a peptide previously discovered by our group that displays cancer-specific cytotoxicity. To design the optimal therapeutic use of the peptide, we identified the intracellular target of CT20p in breast cancer cells, correlating expression patterns of the target with susceptibility to CT20p. Experimental Design: Using polymeric nanoparticles to deliver CT20p, we ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 46 publications
7
79
0
Order By: Relevance
“…responsible for folding 5-10% of the cell proteome, and it is the essential chaperone for folding actin and tubulin into their native forms. CCT inhibition results in the changes in cytoskeletal dynamics and inhibition of actin and tubulin polymerization that we observed in CT20p-treated cells 21-22. Our studies and that of others have reported that CCT is overexpressed in cancer cells and could be an indicator of cancer progression and metastasis 23-26, which makes it a novel target for cancer therapeutics.…”
Section: Introductionsupporting
confidence: 69%
“…responsible for folding 5-10% of the cell proteome, and it is the essential chaperone for folding actin and tubulin into their native forms. CCT inhibition results in the changes in cytoskeletal dynamics and inhibition of actin and tubulin polymerization that we observed in CT20p-treated cells 21-22. Our studies and that of others have reported that CCT is overexpressed in cancer cells and could be an indicator of cancer progression and metastasis 23-26, which makes it a novel target for cancer therapeutics.…”
Section: Introductionsupporting
confidence: 69%
“…Recent work has implicated disruption of the cytoskeleton in the efficacy of CT20, a peptide demonstrating selective cancer‐cell toxicity . Importantly, TRiC has been identified as the target of CT20; TRiC overexpression in breast cancer cell lines is required for increased susceptibility to CT20 …”
Section: Discussionmentioning
confidence: 99%
“…another class of protein-folding complexes, called chaperonins, gained interest with the recognition that cancer cells highly express these mediators of protein-folding [14][15][16][17][18][19][20][21][22][23] . The cytosolic, eukaryotic chaperonin-containing TCP-1 (CCT) is an emerging player in neoplastic transformation with potential for development as a novel diagnostic marker and therapeutic target.…”
mentioning
confidence: 99%
“…Our lab discovered a CCT inhibitor called CT20p that kills cancer cells in a CCT-dependent manner. Cancer cells in which CCT was inhibited were resistant to CT20p killing, while cells in which CCT was increased were susceptible 14,16 . However, the complexity of CCT, with its multiple subunits, and the lack of a full understanding of CCT substrate selectivity in vivo, are some of the challenge that hinder the development of promising therapeutics like CT20p.…”
mentioning
confidence: 99%